Safe Diffusion of Provenance in Wireless Sensor Networks Using in-Packet Bloom Filter Provenance Encoding Technique - P Lal, Sujesh; M. Joe Prathap, P (International Journal of Engineering and Technology, 2018)
Wireless Sensor Networks (WSN) comprises of tiny wireless sensor nodes for continuous observation of physical or environmental Â Â Â Â Â Â Â Â Â Â Â Â Â Â conditions. Sensor networks are increasingly deployed in decision-making infrastructures. They are widely used for battlefield Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â monitoring systems and Supervisory Control and Data Acquisition (SCADA) systems. Making decision makers aware of the trustÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â worthiness of the collected data is crucial. WSNs are used by Business Applications. These applications depend on trustworthy sensor data to control business processes. It is important to ensure the trustworthiness of the data generated from sensor nodes so that effective decisions can be made. Making decision makers aware of the trustworthiness of the collected data is crucial. WSNs are used by Business Applications. These applications depend on trustworthy sensor data to control business processes.We have proposed a different approach for provenance diffusion for WSN using Bloom filters. The major security attributes of the scheme are freshness, confidentiality and integrity. Experimental characteristics and results evaluating the scheme output the efficiency of the provenance encoding and its transmission. Â Â